Analisis Prosedur Ekspor dengan Pendekatan Metode Less Than Container Load: Studi Kasus PT. Konesia Prologix Line - Adawiyah, Ni'matullah; Poernomo, Baby Sri (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2022)
In this modern era, logistics activities will be more efficient and much easier if the management is handed over to the Freight Forwarder. Freight Forwarders can assist export activities such as preparing export documents, cargo consolidation, and can also act as operators and are fully responsible for carrying out transportation even though they do not have their own ships. One of the Freight Forwarders located in central Jakarta, namely PT Konesia Prologix Line, has taken care of the shipment process using the Less Than Container Load (LCL) method, which in this case there are still deficiencies in terms of delivery, therefore it is rarely used by exporters. Therefore this research will discuss the procedures for sending export goods using less than container load (LCL).  This study used a qualitative case study method, namely taking one case to be analyzed in depth so that the data collection carried out was an interview or interview process. With as many as 4 informants. Conducted in July 2022.  The results showed that the export procedure with the LCL method approach at PT Konesia Prologix Line that PT Konesia Prologix Line as a local scale transportation service EMKL and acts as the person in charge of all links in the transportation chain from the beginning to the final destination. The process of managing documents and ending with the process of submitting documents to exporters to booking schedules for delivery of goods